Development of Virtual Reality Laboratory Integrated with Artificial Intelligence for Acid-Base Titration Practicum - Nova Irawati Simatupang; Elferida Sormin; Leony Sanga Lamsari Purba; Nelius Harfa; Adi Nugroho (Postgraduate, University of Mataram, 2025)
The development of technology-based learning platforms and media has been widely carried out; however, most of efforts primarily focus on increasing student interest, while less attention is given to enhancing skills and scientific thinking processes. The purpose of this research was to develop a technology – based learning media, namely a Virtual Reality (VR) laboratory integrated with Artificial Intelligence (AI) to support students’ scientific thinking skills and processes. The AI - integrated VR laboratory was specifically developed for the implementation of acid-base titration practicums. The research followed the ADDIE development model. During the implementation phase, the product was tested on 31 students from Chemistry Education Study Program at UKI, selected using a random sampling technique. Data collection, particularly for product evaluation, was conducted using a non-test instrument in the form of a Likert scale questionnaire. The instrument consisted of indicators of usefulness, efficiency, and interest which were share via Google Form link. Before being distributed to student, the instrument has been validated by an expert validator with a background in chemistry learning media. The results of the analysis indicated that the AI-integrated VR laboratory received positive response from students with a percentage level of 80.79% for the usefulness indicator, 77.06% for the efficiency indicator, and 79,45% for the interest indicator. Therefore, the result of the development of VR laboratory integrated with AI can be considered as a viable alternative learning media for conducting acid-base titration practicum.